Estimation of surface runoff potential using SCS-CN method integrated with GIS approach in Nawagarh watershed of Seonath Sub-Basin, Chhattisgarh - MANIKPURI, SHIVANGI; TRIPATHI, M.P. (Journal of Soil and Water Conservation, 2026)
The present study explores the integration of the SCS-CN approach with RS (Remote Sensing) and GIS (Geographic Information System) environments to enhance model performance. The findings indicate that GIS is the most effective tool for generating thematic maps used in the SCS-curve number approach. The present research work is carried out in Nawagarh watershed which is originated from the Seonath river catchment within the Mahanadi basin in the Indian state of Chhattisgarh covering an area of 2647.27 square kilometers. The drainage exits at Nandghat in the Bemetara district, a part of the Seonath river Sub-basin in the Mahanadi basin. The most important hydrologic factor in the assessment of water resources is rainfall and runoff. The SCS-CN method continues to be widely used and highly regarded. The runoff curve number (CN) is a critical component of this method and is influenced by factors such as land use/land cover (LULC), soil type, and antecedent soil moisture (AMC). Additionally, the SCSCN model requires several essential inputs, including Hydrological Soil Characteristics (HSG), precipitation (P), Antecedent Moisture Condition (AMC), and Weighted Curve Number (WCN). A study has been carried using daily rainfall data from 2012 to 2022. It was found that 1186.27 mm of rainfall occurred on average per year over this period. As a result, the average yearly runoff from 2012 to 2022 was 248.08 mm. The watershed and its runoff flow characteristics are understood by the use of the developed rainfall–runoff model. The management of land and water resources may additionally benefit from the surface runoff potential calculated using the SCS-CN approach.